Inhibition of A2B Adenosine Receptor Attenuates Intestinal Injury in a Rat Model of Necrotizing Enterocolitis - Lie Huang; Juan Fan; Yan-Xiang Chen; Jian-Hui Wang (Mediators of Inflammation)
Necrotizing enterocolitis (NEC) is a lethal gastrointestinal tract disease that occurs in premature infants. Adenosine receptor A2B (A2BR) regulates the inflammation cytokine secretion and immune cell infiltration in the colonic pathophysiology conditions. In the present study, we aim to determine the roles of A2BR in the development of NEC. A NEC rat model was established and treated with A2BR agonist-BAY60-6583 or A2BR antagonist-PSB1115. Animals in the control group were free from any interventions. Our results showed that the inhibition of A2BR PSB1115 improved intestinal injury and inflammation in newborn NEC rats. The expression levels of caspase-3 and the ratio of apoptotic cells were upregulated in NEC rats, and these indices were downregulated after treating with PSB1115 but further upregulated by BAY60-6583. Meanwhile, a similar trend was also witnessed in the changes of MPO activities and proinflammatory cytokines including IL-6, IFN-γ, and TNF-α. However, the anti-inflammatory cytokine IL-10 in the NECP group was significantly higher than that in the NEC and NECB groups (p<0.05, respectively). Moreover, the expression of Ki67 was significantly increased in the NECP group as compared with those of the NEC and the NECB groups (p<0.05, respectively). Collectively, our study suggested that the inhibition of A2BR attenuates NEC in the neonatal rat, at least partially through the modulation of inflammation and the induction of epithelial cell proliferation.